Trading VIX derivatives : trading and hedging strategies using VIX futures, options, and exchange-traded notes - Rhoads, Russell (Wiley, John Wiley & Sons, Inc., 2011)
"Trading VIX Derivatives will be a comprehensive book covering all aspects of the Chicago Board Options Exchange stock market volatility index. The book will explain the mechanics and strategies associated with trading VIX options, futures, exchange trading notes and options on exchange traded notes. Known as the "fear index" the VIX provides a snapshot of expectations about future stock market volatility and generally moves inversely to the overall stock market. As such, many market participants look at the VIX to help understand market sentiment and predict turning points. With a slew of VIX index trading products now available, there are a variety of strategies traders use to speculate outright on the direction of market volatility or to use the products in conjunction with other instruments to create spread trades or hedge their overall risk. A top instructor at the CBOE's Options Institute, the author will reflect the wide range of uses associated with the VIX and will make the book useful to both new traders and seasoned professionals"-- Resumé vydavatele
Obsahuje rejstřík
Keywords: finanční deriváty; opce (finance); burzovní obchody; derivative securities; options (finance); stock exchange transactions; monografie; monographs